2021
DOI: 10.3389/fped.2021.674716
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Antibiotic Prophylaxis Induces Rapid Modifications of the Gut Microbiota in Infants With Vesicoureteral Reflux

Abstract: Background and Objectives: Maturation of the gut microbiota (GM) in infants is critically affected by environmental factors, with potential long-lasting clinical consequences. Continuous low-dose antibiotic prophylaxis (CAP) is the standard of care for children with vesicoureteral reflux (VUR), in order to prevent recurrent urinary tract infections. We aimed to assess short-term GM modifications induced by CAP in infants.Methods: We analyzed the GM structure in 87 infants (aged 1-5 months) with high-grade VUR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…This condition could lead to the selection of pathogenic bacteria that could migrate from the intestine to the urinary tract and could cause short-term recurrence. In the same study, it was also found that the intestinal biodiversity of patients receiving prophylactic therapy for UTIs with trimethoprim-sulfamethoxazole, for vesicoureteral reflux, does not differ over time from that of children without urinary tract abnormalities; this conclusion is limited to the use of that particular type of antibiotic, and in the literature there are conflicting opinions: as the negative effect on the microbiota of antibiotic prophylaxis is well described [ 21 ], starting from the first doses and regardless of dosage, but there is also opposite evidence obtained from pediatric studies on children with urinary tract abnormalities [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This condition could lead to the selection of pathogenic bacteria that could migrate from the intestine to the urinary tract and could cause short-term recurrence. In the same study, it was also found that the intestinal biodiversity of patients receiving prophylactic therapy for UTIs with trimethoprim-sulfamethoxazole, for vesicoureteral reflux, does not differ over time from that of children without urinary tract abnormalities; this conclusion is limited to the use of that particular type of antibiotic, and in the literature there are conflicting opinions: as the negative effect on the microbiota of antibiotic prophylaxis is well described [ 21 ], starting from the first doses and regardless of dosage, but there is also opposite evidence obtained from pediatric studies on children with urinary tract abnormalities [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient in Group 3 was the only person consuming antibiotics with low-dose macrolide therapy. Morello et al reported that infants with vesicoureteral reflux who received continuous low-dose antibiotic prophylaxis (CAP) had higher levels of Enterobacteriaceae and Bacteroidetes than non-CAP infants, and CAP clearly altered the composition of the gut microbiota [55]. This characteristic gut microbiota of Group 3 may be due to the antibiotic's medication, with low-dose macrolide therapy, in addition to the medical condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Blood and stool samples were collected and analyzed in the laboratories of the University of Bologna. For GM profiling, microbial DNA was extracted from 250 mg of each fecal sample using the repeated bead-beating protocol, as previously reported [ 32 ]. The V3–V4 hypervariable regions of the 16S rRNA gene were amplified using the universal primers 341F and 785R with Illumina adapter overhang sequences, and libraries were purified and indexed according to manufacturer’s instructions (Illumina, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Sequence reads were deposited in the National Center for Biotechnology Information Sequence Read Archive (NCBI SRA; BioProject ID PRJNA852514). All sequence data were processed using a pipeline combining PANDASeq [ 32 ] and QIIME 2 [ 33 ]. Briefly, quality-filtered reads were binned into Amplicon Sequence Variants (ASVs) using DADA2 [ 34 ].…”
Section: Methodsmentioning
confidence: 99%